2023
DOI: 10.1002/cbic.202200796
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Metal Complexes for Antimicrobial Photodynamic Therapy

Abstract: Antimicrobial resistance (AMR) is a growing global problem with more than 1 million deaths due to AMR infection in 2019 alone. New and innovative therapeutics are required to overcome this challenge. Antimicrobial photodynamic therapy (aPDT) is a rapidly growing area of research poised to provide much needed help in the fight against AMR. aPDT works by administering a photosensitizer (PS) that is activated only when irradiated with light, allowing high spatiotemporal control and selectivity. The PS typically g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 87 publications
(187 reference statements)
0
29
0
Order By: Relevance
“…Although there are many studies on photodynamic therapy with metal complexes in the literature, there are limited studies on PDAT. 49,50 Finally, BPI derivates can be used as photosensitizer agents for PDAT in drug industry. We hope that this work will lead to our future work on how to tune the properties of these compounds for PDAT by metal and substituent selection in novel N , N , N pincer-type compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are many studies on photodynamic therapy with metal complexes in the literature, there are limited studies on PDAT. 49,50 Finally, BPI derivates can be used as photosensitizer agents for PDAT in drug industry. We hope that this work will lead to our future work on how to tune the properties of these compounds for PDAT by metal and substituent selection in novel N , N , N pincer-type compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its inherent resistance to antimicrobial substances, microbial biofilm poses a significant clinical concern and has been strongly linked to infections in catheterized patients. 50 Few substances have been identified that can inhibit biofilm formation, so it is clear that new strategies are needed to overcome microbial resistance. 1b , 2b , 3b , and 4b compounds were investigated to evaluate the biofilm inhibition abilities against well-known biofilm-forming bacteria, S. aureus and P. aeruginosa .…”
Section: Resultsmentioning
confidence: 99%
“…3–5 Unfortunately, while antibiotics gained popularity as a rapid and simple treatment for infectious illness, the overuse and abuse of these drugs have resulted in the development of significant antimicrobial resistance (AMR). 6,7 More than one million deaths worldwide in 2019 were attributed to antimicrobial resistance (AMR). 8 O'Neill et al reported that without any intervention, about 10 million people per annum will die from antimicrobial-inducing drug-resistance infections by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…9 Henceforth, the development of novel antibacterial agents with new antibacterial mechanisms has become essential to overcome AMR. 6,10,11 Recently, antibacterial photodynamic therapy (aPDT), a non-invasive therapy, has offered significant promises to overcome the AMR problem. 6,10,11 This therapy is also reported to reduce bleeding and inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation